A Fatal Presentation of Dermatomyositis - Khatiwoda, Prasana; Kayastha, SR; Khatiwada, P; Giri, A; Baral, S; Bista, D; Pant, P (Kathmandu University Medical Journal, 2013)
Dermatomyositis (DM) is an autoimmune disease that mainly affects the skin, muscle, and lung. The pathogenesis of skin inflammation in DM is not well understood. We present a 40-year-old male who presented with four months history of generalized skin lesion, pain and weakness. He had elevated transaminases with detectable muscle weakness. This case highlights the need to consider dermatomyositis with skin lesion and weakness; and the use of aggressive immunosuppressive therapies due to its associated vasculopathies. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 78-82 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8027